The effect of unemployment on care provision - Björn Fischer; Peter Haan; Santiago Salazar Sanchez (The Journal of the Economics of Ageing, 2022)
In this paper we estimate the effect of unemployment on informal care provision. For the identification we use plant closures as a source of exogenous variation and combine difference-in-differences with matching based on entropy balancing. The analysis is based on data from the German Socio-Economic Panel (SOEP). We find that there is a time conflict between employment and informal care provision. Unemployment increases the probability of providing care by 2.9 percentage points while the daily hours of care provision rise by around 0.05 h per week-day. Both men and women react with significant increases in care provision. We find the largest effects for women with low education.
Keywords: I11; I18; I38; J14; J21; J22; 330; Long-term care; informal care; long-term care insurance; labor supply; unemployment; plant closure; entropy balancing